Performance degradation mechanisms in small hydropower plants: Field evidence and rotor-bearing integrity analysis from Nepal - Pandey, Roshan; Shrestha, Rajendra; Bhattarai, Nawraj; Paudyal Sharma, Prashant; Tamling, Niharika; Pathak, Kalpana (Journal of Innovations in Engineering Education, 2026)
Hydropower represents nearly 70% of Nepal’s installed capacity via small hydropower plants (SHPs), yet these facilities face an average 12% annual energy loss. While performance degradation is often attributed to hydrological variability, this study demonstrates that 50% of operational issues stem from mechanical degradation. The main aim of the research is to examine and evaluate the mechanical issues in SHPs, especially in shaft, bearing and runner with field based and onsite testing further validation with simulation. This research studies the current status of mechanical performance in SHPs of Nepal exploring its issues and possible causes. The field survey was done during the rainy season (August/September), when water flow is high, and most plants are operating fully. Status of 12 components of plants like bearing, flywheel, turbine, generator, guide valve, penstock, breaker, mechanical governor, transformer has been carried out in 12 plants. Therefore, we primarily focused on issue-oriented selection—narrowing the study from 12 samples to 4 for performance analysis, and then selecting 2 (different capacities) for detailed examination. Technical survey was performed on 12 SHPs with field diagnostics like thermography and vibration analysis along with Finite Element Method (FEM) simulations, this research evaluates mechanical integrity at the ageing Panauti (2.4 MW) and modern Chameliya (30 MW) facilities on issue-oriented basis. Results indicate that high-speed shafting at Panauti facilitates bearing temperatures exceeding 67°C and misalignments over 2 mm. At Chameliya, findings reveal 1.2 mm shaft erosion and significant grid frequency deviations of up to ±13.1%. FEM simulations validate field data, identifying 2X harmonic peaks as the primary diagnostic signature for shaft misalignment, resulting in a 40% vibration amplitude increase. The study concludes that irregular maintenance and systemic design flaws are critical bottlenecks. It recommends holistic rehabilitation and the adoption of robust, maintenance-free components to ensure operational reliability in developing regions.